Formulate and Apply Plant Growth Promotion Rhizobacteria (PGPR) as Biofertilizer and Bioprotectant on Shallot Plantations - Rosmini Rosmini; Nur Hayati; Sri Anjar Lasmini; Hasriyanty Hasriyanty; Irwan Lakani; Burhanuddin Haji Nasir (Journal of Community Practice and Social Welfare, 2022)
UPT Bulupountu Jaya is the one of many shallots or red onions and other vegetables production center in Sigi Regency. The farmers rely heavily on pesticide and chemical fertilizer in their business. Even, the residual pesticide on the plant is beyond permitted standard. The main factor is the lack of awareness and skills of the farmers towards environment-based cultivations and pest control. Our community service with regional featured product schematics, aim to spread the information about the technology of formulation and application of Plant Growth Promoting Rhizobacteria (PGPR) as biofertilizer and bioprotectant on red onion plantations. The methods that were going to be implemented, there are training, demonstration plot of technology application, and assistances. The result of our community service, shows that participants are really into this daily program in the moment, shown by the activeness of participants at various stages of activity. This program of our community service increases the farmers skill points to create own PGPR. For the clearest, about 70% participants increased their knowledge and skill to create PGPR and about 60% participants have had interest to develop and apply PGPR as biofertilizer. As doing so, we expect independent of the farmers from being rely on chemical inputs on red onion plantations.